Efektifitas Digital Marketing Dalam Meningkatkan Kepuasan Dan Loyalitas Pelanggan - Nadia Nur Thahirrah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The development of technology produces increasingly sophisticated means, which can be used as a medium in the development of customer satisfaction-oriented business ventures. One form of integration of such technology is in marketing practices using digital marketing strategies. The purpose of this research is to conceptually examine application-based digital marketing strategies to improve customer satisfaction. This type of research is descriptive with a qualitative approach. Research data is secondary data in the form of theories and empirical findings of previous research obtained using literature studies. Conclusions that can be drawn from the results of discussions state that the integration of application-based digital marketing strategies in a business requires the analysis of internal and external factors to determine the most appropriate digital marketing strategy.